High quality transparent conductive Ag-based barium stannate multilayer flexible thin films - Muying Wu (Nature Portfolio, 2017)
Abstract Transparent conductive multilayer thin films of silver (Ag)-embedded barium stannate (BaSnO3) structures have been deposited onto flexible polycarbonate substrates by magnetron sputtering at room temperature to develop an indium free transparent flexible electrode. The effect of thicknesses of Ag mid-layer and barium stannate layers on optical and electrical properties were investigated, and the mechanisms of conduction and transmittance were discussed. The highest value of figure of merit is 25.5 × 10−3 Ω−1 for the BaSnO3/Ag/BaSnO3 multilayer flexible thin films with 9 nm thick silver mid-layer and 50 nm thick barium stannate layers, while the average optical transmittance in the visible range from 380 to 780 nm is above 87%, the resistivity is 9.66 × 10−5 Ω · cm, and the sheet resistance is 9.89 Ω/sq. The change rate of resistivity is under 10% after repeated bending of the multilayer flexible thin films. These results indicate that Ag-based barium stannate multilayer flexible thin films can be used as transparent flexible electrodes in various flexible optoelectronic devices.